2002
DOI: 10.1002/1099-0690(200203)2002:5<941::aid-ejoc941>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Allylic CH Oxidation versus Epoxidation of 2-Cyclohexenols, Catalyzed by Chromium- and Manganese-Substituted Polyoxometalates and Salen Complexes

Abstract: 2-Cyclohexenol (1) is oxidized chemoselectively to 2-cyclohexenone (2a) by the α-Keggin chromium-substituted polyoxometalate (POM) Ia as the catalyst and iodosobenzene as the oxygen source. For the chromium(salen) catalyst IIa the same chemoselectivity in favor of allylic CH oxidation is observed. The manganese-substituted POM Ib and the manganese(salen) complex IIb, however, afford appreciable amounts of the epoxy alcohol 2b. For the stereolabeled 5-tert-butyl-2-cyclohexenols 5, the diastereoselectivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Tungsten (W)- and niobium (Nb)-based catalysts have shown promising performances for liquid-phase oxidation of olefins (Figure ). W-based catalysts have attracted extensive interest because they have been widely employed in selective oxidation of alkenes and alcohols, olefin metathesis, oxidative cleavage of olefins, dehydration, oxidative desulfurization of sulfur-containing organics, and acid catalyzed reactions such as isomerization. In order to achieve higher performance, recent efforts have been paid on proposing novel synthetic approaches for catalysts preparation, many of which focus on the formation of mesoporous and nanostructured oxides and incorporation of active metal sites into inorganic matrices such as siliceous and nonsiliceous mesostructured materials. For example, reported heterogeneous catalysts include tungsten oxide (WO 3 ) containing mesoporous materials synthesized by means of a number of synthetic approaches, heterogenized polyoxotungstates and W complexes, as well as W exchanged layered double hydroxides.…”
Section: Background Of W and Nb Catalystsmentioning
confidence: 99%
“…Tungsten (W)- and niobium (Nb)-based catalysts have shown promising performances for liquid-phase oxidation of olefins (Figure ). W-based catalysts have attracted extensive interest because they have been widely employed in selective oxidation of alkenes and alcohols, olefin metathesis, oxidative cleavage of olefins, dehydration, oxidative desulfurization of sulfur-containing organics, and acid catalyzed reactions such as isomerization. In order to achieve higher performance, recent efforts have been paid on proposing novel synthetic approaches for catalysts preparation, many of which focus on the formation of mesoporous and nanostructured oxides and incorporation of active metal sites into inorganic matrices such as siliceous and nonsiliceous mesostructured materials. For example, reported heterogeneous catalysts include tungsten oxide (WO 3 ) containing mesoporous materials synthesized by means of a number of synthetic approaches, heterogenized polyoxotungstates and W complexes, as well as W exchanged layered double hydroxides.…”
Section: Background Of W and Nb Catalystsmentioning
confidence: 99%
“…Styrene oxide was detected, but yields were <1%. Adam et al showed that 2-cyclohexenol is oxidized exclusively to 2-cyclohexenone by a Cr(salen) complex . Koner et al epoxidized norbornene with catalyst 1 and tert -butylhydroperoxide for comparison to immobilized versions …”
Section: 14 Other Achiral Cr(salen)-mediated Epoxidationsmentioning
confidence: 99%
“…Later studies using cyclodextrins to precoordinate the substrate were less successful . Adam et al reported evidence that demonstrates that precoordination is important in the epoxidation of allylic alcohols by Mn(salen) complexes. , …”
Section: 25 Other Mn(salen)-catalyzed Achiral Epoxidationsmentioning
confidence: 99%
“…In general, various criteria concerning the metal species need to be considered prior to the incorporation of the metals into the support. For instance, allylic CH bond oxidation has been studied using different transition metals such as Cr, Co, Mn, and Cu . Among them, Cu grafted into the mesoporous silica via APTMS resulted in high catalytic efficiency due to its attractive properties, such as high yield, cost‐effectiveness, and recyclability, as well as its recovery ability .…”
Section: Potential Applicationsmentioning
confidence: 99%